An Application of Geophysical Methods Before Borehole Drilling at PT Great Giant Pineapple’s Pineapple Plantation: - - Santoso, Nono Agus (Fakultas Teknik Universitas Lampung, 2025)
Groundwater is a vital resource for the sustainability of agricultural production in pineapple plantations (Ananas comosus) owned by PT Great Giant Pineapple (GGP), Central Lampung. High water demand during the dry season requires an efficient and accurate aquifer exploration system to avoid blind drilling. This study aims to apply geophysical competence in determining the location and depth of potential aquifer layers before drilling a borehole using the SX300 Multichannel Audio-frequency Magnetotelluric (ADMT) method. The results obtained are the importance of applying geophysical competence before drilling a borehole. Based on the ADMT results, the location of the aquifer on track 1 is at the 11th electrode with an aquifer depth of around 10-160 m. While on track 2, the location of the aquifer at the 2nd electrode with an aquifer depth of around 10-150 m. These results are recommendations for PT GGP in determining the point of drilling a deep well at a depth of 50-150 m.